Efflux Pump-Mediated Quinolone Resistance in Staphylococcus aureus Strains Wild Type for gyrA, gyrB, grlA, and norA - Muñoz-Bellido, Juan Luis (American Society for Microbiology, 1999)
Fluoroquinolone efflux was studied in 47 Staphylococcus aureus clinical strains with MICs of ciprofloxacin (CFX) of ≤2 μg/ml. Forty-three strains were wild type for gyrA, gyrB, and grlA quinolone resistance-determining regions and for norA and its promoter region. Forty of these strains (MICs of CFX, 0.1 to 0.2 μg/ml) did not show efflux of fluoroquinolones. Three strains (MICs of CFX, 1 to 2 μg/ml) showed efflux. These results suggest that efflux can appear in S. aureus clinical strains in the absence of mutations in norA and its promoter.